The Gonadotropin-Releasing Hormone Analogue Therapy May Not Impact Final Height in Precocious Puberty of Girls With Onset of Puberty Aged 6 - 8 Years - Korkmaz, Ozlem (J Clin Med Res, 2019)
BACKGROUND: The effect on final height of gonadotropin-releasing hormone analogues (GnRHa) used in the treatment of precocious puberty is controversial. The aim of this study was to determine whether or not GnRHa therapy would make any contribution to final height in precocious puberty of girls with onset of pubertal characteristic development aged 6 - 8 years. METHODS: Age at start of puberty, target height standard deviation score (SDS) presentation, follow-up height SDS, body mass index (BMI) SDS, bone age and predicted adult height of 34 female subjects who had reached their final height and with pubertal findings beginning at the ages of 6 - 8 were evaluated. These subjects were divided into two groups: treatment and non-treatment groups. The treatment group was further divided into two subgroups, receiving monthly or three-monthly depot GnRHa. RESULTS: Age at onset of puberty was 7.2 ± 0.9 years. Twenty-five cases were started on GnRHa and nine were followed-up without treatment. Fourteen cases received monthly 3.75 mg depot triptorelin acetate and 11 received three-monthly 11.25 mg depot. Mean age at start of treatment in the treatment group was 9.1 ± 1.2 years and mean bone age was 9.7 ± 2.3 years. Age at presentation in the non-treatment group was 8.4 ± 1.4 years and bone age was 10.3 ± 2.1 years. Target and final height SDS were similar in all the groups (P > 0.05). No difference was determined between the treatment groups in terms of initial height SDS, bone age, length of treatment, final height SDS or BMI SDS (P > 0.05). CONCLUSIONS: GnRHa therapy did not make a positive contribution to final height in precocious puberty of girls with onset of puberty aged 6 - 8 years.